HATCH Score and Left Atrial Size Predict Atrial High-Rate Episodes in Patients With Cardiac Implantable Electronic Devices - Chen, Ju-Yi; Chen, Tse-Wei; Lu, Wei-Da (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients with sustained atrial high-rate episodes (AHRE) have a high risk of major adverse cardio/cerebrovascular events (MACCE). However, the prediction model and factors for the occurrence of AHRE are unknown. We aimed to identify independent factors and various risk models for predicting MACCE and AHRE. Methods: We retrospectively enrolled 314 consecutive patients who had cardiac implantable electronic devices (CIEDs). The primary endpoint was MACCE after AHRE ≥3, 6 min, and 6 h. Atrial high-rate episodes was defined as >175 bpm (Medtronic®) lasting ≥30 s. Multivariate Cox and logistic regression analysis with time-dependent covariates were used to determine variables associated with independent risk of MACCE and occurrence of AHRE ≥3 min, respectively. Results: One hundred twenty-five patients (39.8%) developed AHRE ≥3 min, 103 (32.8%) ≥6 min, and 55 (17.5%) ≥6 h. During follow-up (median 32 months), 77 MACCE occurred (incidence 9.20/100 patient years, 95% CI 5.66–18.39). The optimal AHRE cutoff value was 3 min for MACCE, with highest Youden index 1.350 (AUC, 0.716; 95% CI, 0.638–0.793; p < 0.001). Atrial high-rate episodes ≥3 min−6 h were independently associated with MACCE. HATCH score and left atrial diameter were independently associated with AHRE ≥3 min. The optimal cutoff for HATCH score was 3 and for left atrial diameter was 4 cm for AHRE ≥3 min. Conclusion: Patients with CIEDs who develop AHRE ≥3 min have an independently increased risk of MACCE. Comprehensive assessment using HATCH score and echocardiography of patients with CIEDs is warranted.